Serviceability assessment of footbridges in unrestricted pedestrian traffic conditions. Issue 12 (1st December 2016) - Tubino, Federica; Piccardo, Giuseppe
Abstract: A critical analysis of the procedures available in the literature for the serviceability assessment of footbridges in unrestricted pedestrian traffic conditions is presented. Based on a full probabilistic model of the loading, Monte Carlo simulations are carried out and a critical discussion concerning the role of the statistical distribution of the random walking parameters on the footbridge dynamic response is provided. Furthermore, numerical results are compared with the ones obtained by simplified procedures. Finally, a graphical procedure is proposed which permits a simple evaluation of footbridge maximum acceleration as a function of the modal mass, damping ratio and expected average pedestrian flow.